Feminist postcolonial theory : a reader - Lewis, Reina, 1963-; Mills, Sara, 1954- (Edinburgh University Press, 2003)
The readings have been selected to examine the textual and discursive nature of colonial and post-colonial discourse in relation to gender and the material effects of the post-colonial condition and practices developed in relation to it.